2014
DOI: 10.15288/jsads.2014.75.50
|View full text |Cite
|
Sign up to set email alerts
|

Seventy-Five Years of Comorbidity Research

Abstract: ABSTRACT. Objective: As part of the 75th anniversary edition of the Journal of Studies on Alcohol and Drugs, this article reviews research on the relationship between mental disorders and substance use disorders ("comorbidity") from 1940-the journal's inception-to the present. Method: First, a survey of the titles and abstracts of all articles published in the journal was used to identify those articles pertaining to comorbidity. Seminal and representative works from this set of articles and a limited selectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 63 publications
0
4
0
3
Order By: Relevance
“…Research has also focused on the high coincidence of AUD and internalizing disorders [41][42][43] . Previous causal modeling research found a causal path from internalizing disorder to drinking behavior in AUD (mediated through drinking-to-cope) 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Research has also focused on the high coincidence of AUD and internalizing disorders [41][42][43] . Previous causal modeling research found a causal path from internalizing disorder to drinking behavior in AUD (mediated through drinking-to-cope) 44 .…”
Section: Discussionmentioning
confidence: 99%
“…Despite this, the bulk of psychopathology research is still conducted on specific manifestations of comorbidity, or on specific disorders in isolation, as if they are etiologically and pathophysiologically unique (Caspi et al, 2014; Lahey et al, 2011). If this were the case, every possible disorder pairing would also be unique, and would require its own comorbidity model (Kushner, 2014). However, analyses of the correlations among DSM disorders have taught us that, empirically, these disorders are best conceptualized as indicators of the IE spectra.…”
Section: The Case For Moving Beyond Comorbidity As a Focus In Researchmentioning
confidence: 99%
“…Η κατάχρηση αλκοόλ στις σύγχρονες απόψεις θεωρείται ως ένα είδος «αυτοθεραπείας» των ατόμων, στην προσπάθειας τους να αποκαταστήσουν την ηρεμία στον εαυτό τους. Επίσης, υπάρχουν μια σειρά από παθολογικά ιδεοληπτικά και ειδικά καταναγκαστικά στοιχεία χαρακτηριολογικά για κάθε ασθενή, που χρησιμεύουν σαν άμυνα του ατόμου και σχετίζονται με την έννοια του εθισμού [19,145,146].…”
Section: ψυχολογικοί παράγοντεςunclassified
“…Επίσης, σε αυτή τη διαδικασία συνεισφέρει και ενισχύει η κλασσικού τύπου εξάρτηση κατά Παβλόφ. Όπου μέσω της γενίκευσης όπως ο χώρος, τα άτομα του δίνουν την ευκαιρία να συνδυάσει τα θετικά αποτελέσματα και να οδηγηθεί σε ακόμα μεγαλύτερη χρήση αλκοόλ [19,145].…”
Section: ψυχολογικοί παράγοντεςunclassified
See 1 more Smart Citation